The Effectiveness of Mediation in Resolving Public Information Disputes at the East Kalimantan Information Commission - Zakaria, Indra; Duraesa, M. Abzar; Afandi, Nur Kholik; Beta, A Rivai (PT ARRUS Intelektual Indonesia, 2025)
Abstract: Public information disputes often pose challenges in realizing the principles of transparency and government accountability. This study analyzes the effectiveness of mediation as an alternative dispute resolution method at the Information Commission (KI) of East Kalimantan. Mediation was chosen as the focus of this research because it offers a more flexible, faster, and non-litigation approach compared to adjudication. The study employed a qualitative case study method, with data collected through in-depth interviews with KI Commissioners, mediators, and disputing parties (applicants and public bodies). Document analysis of dispute records and KI East Kalimantan annual reports was also conducted. The findings indicate that mediation at KI East Kalimantan is highly effective, with an average success rate of 75% per year over the past three years. Key success factors include: (1) mediator communication skills and neutrality, (2) willingness of parties to negotiate and reach agreements, and (3) a clear regulatory framework empowering KI to facilitate mediation. Nevertheless, challenges remain, such as limited understanding of mediation procedures among disputing parties and constrained human resources within KI East Kalimantan. Despite these challenges, mediation has proven effective in reducing costs, expediting dispute resolution, and preserving good relationships between parties. This study recommends enhancing public awareness of mediation procedures and strengthening mediator capacity to optimize the Information Commission’s role in promoting transparency in East Kalimantan.